The study of acceptance people regarding to environmental graphic design at Planetarium Melaka / Nurul Ashikin Ibrahim - Ibrahim, Nurul Ashikin (2015)
What is the environment? When we talk about the environment we mean everything in the world around us that surrounds and affects all life on earth, including the air, food chains, the water cycle, plants, animals and other humans but did you know definition of environmental graphic design? Environmental Graphic Design (EGD) embraces many design disciplines including graphic, architectural, interior, landscape, and industrial design, all concerned with the visual aspects ofway finding, communicating identity and information . The research of my project is focus on the acceptance people regarding on the environmental graphic design. Environmental graphic design is very important in our daily life because it help to route people, enable them to find their way themselves without asking direction, and prevent people from feeling lost and lonely. This study used survey as a research method to collect data by distributing questionnaire about the acceptance people on environmental graphic design in Planetarium Melaka.